A ODR como protagonista da resolução de conflitos na sociedade 5.0 - Tome, Bruna Borghi (2020)
In this paper ODR (Online Dispute Resolution) will be studied in the framework of the so-called Society 5.0, in which technology is used at the service of mankind in order to contribute to the social well-being. The goal is to verify whether this online form of conflict resolution may be considered a protagonist of dispute resolution methods, contributing to Law 4.0 and to the realization of Society 5.0. To this end, the historical evolution of Procedural Law will be displayed, as well as the concept and scope of the multidoors system. Several examples of ODR tools existing in Brazil and in the world, public or private, will be analyzed, addressing their operation and success data when such data exists. Comparatively, some statistical data from the current judicial system that is facing a stage of overload and slowness will be brought, as well as what is stated by the jurisprudence, the regulation and the doctrine about this subject. Through this method, we may come to understand that ODR can and should be thought as a protagonist and as a contemporary form of dispute resolution that helps to achieve the ideal of access to justice as something fair, timely and appropriate, since faster, cheaper and with significant success rates